1988
DOI: 10.1016/0735-1097(88)90167-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrast echocardiography during coronary arteriography in humans: Perfusion and anatomic studies

Abstract: In humans, the physiologic relation between myocardial blood flow and epicardial coronary artery anatomy remains poorly defined. With the recent development of sonicated microbubble contrast agents, it is now possible to use contrast echocardiography to assess myocardial perfusion and to correlate blood flow with angiographically identified coronary artery anatomy. The purpose of the current study was to determine myocardial perfusion patterns in patients without significant coronary artery disease. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The microbubbles measured 3.8 ± 2.1 f.Lm and no complications were reported. In a further study in 14 patients, Feinstein et al [41] used MC-2DE with sonicated "Renograffin-76" (bubble size 4.5 ± 2.8 f.lm) to determine myocardial perfusion patterns in patients without significant coronary artery disease. No major complications were again reported although there were transient changes in heart rate, blood pressure and ECG during the intracoronary injections.…”
Section: Human Studiesmentioning
confidence: 98%
“…The microbubbles measured 3.8 ± 2.1 f.Lm and no complications were reported. In a further study in 14 patients, Feinstein et al [41] used MC-2DE with sonicated "Renograffin-76" (bubble size 4.5 ± 2.8 f.lm) to determine myocardial perfusion patterns in patients without significant coronary artery disease. No major complications were again reported although there were transient changes in heart rate, blood pressure and ECG during the intracoronary injections.…”
Section: Human Studiesmentioning
confidence: 98%
“…Micrometer-size gas bubbles are exceptional scatters of ultrasound and have been used as intravascular contrast agents for over two decades. 19,20 With our hemispherical array, and using passive beamforming, we can optimize the imaging resolution for a given frequency and achieve sufficient SNR to image single bubbles through a human skullcap. Here we transcranially excite single microbubbles flowing through a tube phantom and generate threedimensional maps of the bubbles, using a bubble-based phase correction technique, similar to those proposed by others for phase correction of the transmit beam, 21,22 but modified to apply to the receive case.…”
Section: Introductionmentioning
confidence: 99%
“…Left heart contrast echocardiography has been performed by injecting contrast agents directly into the aortic root (1,2), the left ventricle (3,4) or the coronary artery (2,(5)(6)(7)(8). Although this technique has been helpful to identify abnormal cardiac structure (1 , 3), determine valvular regurgitation (4), demonstrate left-to-right shunts (4,9) and evaluate myocardial perfusion (2,(5)(6)(7)(8), the insertion of arterial catheters was required.…”
Section: Introductionmentioning
confidence: 99%
“…Although this technique has been helpful to identify abnormal cardiac structure (1 , 3), determine valvular regurgitation (4), demonstrate left-to-right shunts (4,9) and evaluate myocardial perfusion (2,(5)(6)(7)(8), the insertion of arterial catheters was required. Recently, several investigators have reported left heart contrast echocardiography following intrapulmonary, right atrial or peripheral venous injection of contrast agents capable of transpulmonary passage (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%